On the Measurement of Implicative Dilemmas. Issue 3 (3rd July 2019) - Rouco, Víctor; Paz, Clara; Winter, David; Feixas, Guillem
Abstract : The implicative dilemma (ID) is gradually receiving attention of clinical psychologists and researchers. Although research on its clinical relevance is promising, there are still some issues regarding its measurement that need further consideration. This article explores the adequacy of the different thresholds used to determine construct association, the efficacy of the different indices commonly used to measure IDs, and a verification of the ID not being a mere subproduct of the self-ideal distance. It also introduces a new index. Finally, guidelines are provided for practitioners on how to interpret the indices' numerical results in relation to major depression.